E-COMMERCE DAN PROFESI AKUNTAN PUBLIK - Mutiara Kadarwati; Khomsiyah Khomsiyah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2017)
The purpose of this research is to analyze expertise of E-commerce as arequirement of auditor candidate recruitment process; the need for training of Ecommerce to the auditor and the importance of the audit formed a special division Ecommerce. This research used a descriptive - explorative study. The data obtained from 40 respondents, auditors working at the public accounting firms in Jakarta. The sampling technique used for this research is purposive sampling. The results showed that: (1) Most of respondents do not agree an E-commerce expertise as a requisite process of recruiting candidates for auditor, (2) Auditor agree that the need for training E-commerce from within or outside public accounting firmsand (3) Respondents agreed that formed a special division of audit E-commerce with a reason to be more specific.